Isolasi Dan Karakterisasi Flavonoid Antioksidan Dari Herba Meniran (Phyllanthus niruri L.) - Harrizul Rivai; Diyah Permata Sari; Zet Rizal (STIFARM Padang, 2012)
The isolation of flavonoid substance from Meniran has been performed. Of 100 grams of Meniran’s dried powder, 4.286 grams (4.286%) of thick extract, 1.76 grams of n-hexane fraction, 1.91 grams of CHCl3 fraction, 1.8 grams ofethyl acetate fraction, 2.12 grams of butanol fraction and 24.86 grams of residual fraction has been derived. After preparative chromatography,which is to isolate flavonoid, had been performed, it acquired four blotches which were marked as A,B,C and D. And afterwards it was evaporated which resulted 26.9 mg of flavonoid A, 30.4 mg of flavonoid B, 34.6 mg of flavonoid C and 35.4 mg of flavonoid D. Characterization was focused on flavonoid C as it has the highest antioxidant activities which was recognized from its high inhibition persentage which was attained following a DPPH test. flavonoid C is amorf, yellow coloured, and dissipated at 161.8o – 163.2o C. Based on UV spectrum with slide reactor and infrared spectrum, it was assumed that flavonoid C is an aglicone isoflavone which has an –OH on the 5th position and an o-diOH in ring A (6.7 or 7.8).